Bioethanol from cassava: Characterization of starch during thermo-enzymatic hydrolysis - Ku Syahidah, Ku Ismail; Noorulnajwa Diyana, Yaacob; Khairul Farihan, Kasim; Khairul Akhbar, Ahmad Zabidi; Mohamed Zulkali, Mohamed Daud, Prof. Dr. (Universiti Teknologi MARA (UiTM), 2011)
Organized by Universiti Teknologi MARA, 12th - 13th December 2008 at Penang, Malaysia.